EFFECT OF RAMI FIBER IMMERSION DURATION ON SALAM LEAF EXTRACT AS A PRESERVATIVE FOR FISH CATCHING - Poltak Fanjay N. Sitepu; Nofrizal Nofrizal; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe aim of this research is to find out how long the immersion effect of flax fiber on bay leaf extracts is to determine the value of breaking strength and stretching of flax fiber. The method used in this study is an experimental method using a one-factor Complete Tool Design, which is by experimenting the length of time the flax fiber immersion in bay leaf extract as a fishing gear with immersion time for 0 weeks to 12 weeks. The value of breaking strength and elongation of the fibers were tested using Breaking Strength Tester. The value of breaking strength of flax fiber that had been soaked decreased in the 1st and 2nd weeks and then increased every week and the highest peak in the 7th week was 3.35 kgf / mm2 but in the 8th week until the 12th week decreased. The value of flax fibers has increased unstable. The highest peak in the first week is 26.60 mm and the lowest flax fiber in the second week is 21.40 mm. The results are seen that bay leaf extract can increase the value of breaking strength and elongation of flax fiberKeywords: breaking strength, elongation, flax fiber,salam leaf extract